Rare earth doped modified black titanium dioxide supported platinum catalyst, its preparation method and use
Patent Information
- Application Number
- CN202611083868.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]鉴于此,本发明提出了一种稀土掺杂改性黑色二氧化钛负载Pt催化剂及其制备方法和应用,用以解决现有氢还原法制备的黑色二氧化钛负载铂催化剂,因载体氧空位浓度提升受限且反应过程中氧空位易湮灭、铂纳米颗粒与载体的金属 - 载体相互作用较弱而易发生团聚脱落的问题
1.本发明通过对铈掺杂TiO2纳米片进行低温氢等离子体处理,避免了高温处理导致的晶粒烧结;同时后续的高温氢氩气体还原处理通过高温氢氩还原向体相延伸氧空位,结合铈离子的晶格掺杂与晶界偏析作用,既降低了氧空位形成能,又锚定了空位结构、抑制反应过程中的空位湮灭,进而大幅提高了催化剂载体氧空位浓度。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and more specifically, to a rare earth-doped modified black titanium dioxide supported Pt catalyst, its preparation method, and its application. Background Technology
[0002] Glycerol is a major byproduct of biodiesel production. The glycerol molecule contains three hydroxyl functional groups, and through selective oxidation, it can be used to prepare various high-value-added fine chemicals such as glyceric acid, glyceraldehyde, and dihydroxyacetone. Glyceric acid, in particular, possesses both hydroxyl and carboxyl functional groups, exhibiting high chemical reactivity and making it an important raw material in organic synthesis, pharmaceutical intermediates, and food additives.
[0003] Selective oxidation of glycerol often utilizes noble metal catalysts, with platinum-based catalysts being particularly effective because they can catalyze the oxidation of glycerol to free glyceric acid under alkaline conditions, avoiding subsequent acidification. Current technologies, to improve the dispersibility and catalytic performance of platinum active components, typically load platinum nanoparticles onto the surface of metal oxide supports, utilizing the structural and electronic effects of the support to modulate catalytic performance. Black titanium dioxide, with its abundant oxygen vacancy defects, possesses excellent visible light response and electron transport properties; using it as a noble metal catalyst support can effectively regulate metal-support interactions and enhance catalytic activity.
[0004] Chinese patent application CN117504843A discloses a supported catalyst for the selective oxidation of glycerol. It uses spherical, flocculent, or sheet-like black titanium dioxide as a support to load platinum active components. The black TiO2 support is prepared by high-temperature reduction under a hydrogen-argon atmosphere, enabling selective oxidation of glycerol under neutral conditions. However, this technical solution still has the following shortcomings: First, when using a one-step high-temperature hydrogen reduction process to prepare black titanium dioxide, there is a bottleneck in increasing the oxygen vacancy concentration. Excessively high reduction temperatures can easily cause TiO2 grain sintering, and oxygen vacancies are prone to migration and annihilation during the reaction, resulting in insufficient long-term stability of the defect structure. Second, the metal-support interaction between the pure-phase black TiO2 support and platinum nanoparticles is limited. When using traditional liquid-phase chemical reduction methods to load platinum, platinum nanoparticles are prone to agglomeration and growth, limiting the exposure of active sites, and platinum particles are easily detached and lost during the reaction. Therefore, the present invention proposes a method for preparing a rare earth-doped modified black titanium dioxide supported Pt catalyst, which has important practical significance. Summary of the Invention
[0005] In view of this, the present invention proposes a rare earth-doped modified black titanium dioxide supported Pt catalyst, its preparation method and application, to solve the problems of existing black titanium dioxide supported platinum catalysts prepared by hydrogen reduction method, which are prone to agglomeration and shedding due to limited increase in oxygen vacancy concentration on the support, easy annihilation of oxygen vacancy during the reaction, and weak metal-support interaction between platinum nanoparticles and the support.
[0006] This invention proposes a method for preparing a rare earth-doped modified black titanium dioxide supported Pt catalyst, comprising the following preparation steps: Tetrabutyl titanate was mixed with hydrofluoric acid, and a cerium source was added and stirred to obtain a precursor solution. The precursor solution was subjected to a hydrothermal reaction, and the reaction product was washed, dried, and then calcined at high temperature to obtain cerium-doped TiO2 nanosheets. The cerium-doped TiO2 nanosheets were subjected to low-temperature hydrogen plasma treatment followed by high-temperature hydrogen-argon gas reduction treatment to obtain a cerium-doped TiO2 support. The cerium-doped TiO2 support was mixed with ethanol and then added to an aqueous chloroplatinate solution and stirred in the dark to obtain a first mixture. The first mixture was subjected to visible light-induced reduction and post-processing to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0007] Preferably, the volume ratio of tetrabutyl titanate to hydrofluoric acid is (20~30):(2~4), and the mass fraction of hydrofluoric acid is 40%.
[0008] Preferably, the cerium source is cerium nitrate hexahydrate, and the molar ratio of cerium to titanium in the rare earth-doped modified black titanium dioxide supported Pt catalyst is 3%~8%.
[0009] Preferably, the calcination temperature of the high-temperature calcination treatment is 350~450℃, and the calcination time is 1~3h.
[0010] Preferably, the atmosphere for the low-temperature hydrogen plasma treatment is hydrogen, the chamber pressure is 20~60Pa, the radio frequency plasma power is 100~200W, and the treatment time is 10~30min.
[0011] Preferably, the atmosphere for the high-temperature hydrogen-argon gas reduction treatment is a hydrogen-argon mixed gas, the treatment temperature is 700~950℃, the heating rate is 3~8℃ / min, and the holding time is 3~5h.
[0012] Preferably, the platinum loading of the rare earth-doped modified black titanium dioxide supported Pt catalyst is 1% to 3% of the total mass of the catalyst.
[0013] Preferably, the visible light-induced reduction specifically includes: The first mixture was irradiated with visible light with a wavelength ≥420nm, and the incident light intensity was controlled to be 100~200mW / cm². 2 Sodium borohydride aqueous solution is added dropwise during irradiation, wherein the molar ratio of sodium borohydride to platinum in the first mixture is (5~20):1, and the addition time is 8~20 min; after the addition is completed, the light is maintained and the reaction is stirred for 1.5~2.5 h.
[0014] This invention also proposes a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0015] This invention also proposes the application of rare earth-doped modified black titanium dioxide supported Pt catalyst in the catalytic oxidation of glycerol.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention avoids grain sintering caused by high-temperature treatment by subjecting cerium-doped TiO2 nanosheets to low-temperature hydrogen plasma treatment; at the same time, the subsequent high-temperature hydrogen-argon gas reduction treatment extends oxygen vacancies into the bulk phase through high-temperature hydrogen-argon reduction, combined with the lattice doping and grain boundary segregation of cerium ions, which not only reduces the oxygen vacancy formation energy, but also anchors the vacancy structure and inhibits vacancy annihilation during the reaction process, thereby significantly increasing the oxygen vacancy concentration of the catalyst support.
[0017] 2. This invention employs visible light-induced reduction, utilizing the visible light response characteristics of black TiO2 itself. Under illumination, photogenerated electrons are enriched in oxygen vacancies and cerium active sites, driving the platinum precursor to preferentially nucleate and grow in situ at defect sites. Simultaneously, the in-situ grown platinum particles form a strong metal-support interaction with the support, significantly enhancing the interfacial electron transfer effect and effectively strengthening the catalyst's ability to oxidize and activate the primary hydroxyl groups of glycerol. Detailed Implementation
[0018] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0019] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0020] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0021] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0022] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0023] This invention provides a method for preparing a rare earth-doped modified black titanium dioxide supported Pt catalyst, comprising the following preparation steps: Tetrabutyl titanate was mixed with hydrofluoric acid, and a cerium source was added and stirred to obtain a precursor solution. The precursor solution was subjected to a hydrothermal reaction, and the reaction product was washed, dried, and then calcined at high temperature to obtain cerium-doped TiO2 nanosheets. The cerium-doped TiO2 nanosheets were subjected to low-temperature hydrogen plasma treatment followed by high-temperature hydrogen-argon gas reduction treatment to obtain a cerium-doped TiO2 support. The cerium-doped TiO2 support was mixed with ethanol and then added to an aqueous chloroplatinate solution and stirred in the dark to obtain a first mixture. The first mixture was subjected to visible light-induced reduction and post-processing to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0024] Specifically, the stirring time after adding the cerium source is preferably 5 to 15 minutes; Specifically, the hydrothermal reaction involves transferring the precursor solution to a high-pressure reactor, sealing it, and then subjecting it to a hydrothermal reaction at 160-200°C for 18-30 hours. After the reaction is complete, the mixture is allowed to cool naturally to room temperature.
[0025] Specifically, when washing and drying the reaction product, the washing and drying process involves: alternating centrifugation and washing with anhydrous ethanol and deionized water 2 to 4 times, followed by constant temperature drying at 60 to 80°C for 8 to 16 hours after washing.
[0026] Specifically, when the cerium-doped TiO2 support is mixed with ethanol, the ethanol is anhydrous ethanol, and the solid-liquid ratio of the cerium-doped TiO2 support to ethanol is 1g:(100~200)mL.
[0027] Specifically, the stirring time in the dark is 20-40 minutes.
[0028] Specifically, the post-processing involves centrifuging the product after visible light-induced reduction, washing it 2-4 times alternately with distilled water and anhydrous ethanol, and then drying it at a constant temperature of 50-70°C for 10-14 hours.
[0029] It is understood that this invention avoids grain sintering caused by high-temperature treatment by treating cerium-doped TiO2 nanosheets with low-temperature hydrogen plasma; at the same time, the subsequent high-temperature hydrogen-argon gas reduction treatment extends oxygen vacancies into the bulk phase through high-temperature hydrogen-argon reduction, combined with the lattice doping and grain boundary segregation of cerium ions, which not only reduces the oxygen vacancy formation energy, but also anchors the vacancy structure and inhibits vacancy annihilation during the reaction process, thereby significantly increasing the oxygen vacancy concentration of the catalyst support.
[0030] It is understood that the present invention employs visible light-induced reduction, utilizing the visible light response characteristics of black TiO2 itself. Under illumination, photogenerated electrons are enriched in oxygen vacancies and cerium active sites, driving the platinum precursor to preferentially nucleate and grow in situ at defect sites. At the same time, the in-situ grown platinum particles form a strong metal-support interaction with the support, significantly enhancing the interfacial electron transfer effect and effectively strengthening the catalyst's ability to oxidize and activate the primary hydroxyl groups of glycerol.
[0031] In this invention, the volume ratio of tetrabutyl titanate to hydrofluoric acid is (20~30):(2~4), and the mass fraction of hydrofluoric acid is 40%; preferably, the volume ratio of tetrabutyl titanate to hydrofluoric acid is 25:3, and the mass fraction of hydrofluoric acid is 40%.
[0032] Understandably, 40% hydrofluoric acid by mass acts as a crystal face etching and morphology control agent in the hydrothermal reaction. Fluoride ions can be selectively adsorbed on specific crystal faces of the titanium dioxide precursor, inhibiting the growth rate of the crystal face and inducing preferential growth of the crystal along the two-dimensional direction to form a uniformly morphological sheet-like titanium dioxide nanostructure.
[0033] In this invention, the cerium source is cerium nitrate hexahydrate, and the molar ratio of cerium to titanium in the rare earth-doped modified black titanium dioxide supported Pt catalyst is 3%~8%; the preferred molar ratio of cerium to titanium in the rare earth-doped modified black titanium dioxide supported Pt catalyst is 5%.
[0034] Understandably, cerium nitrate hexahydrate exhibits good solubility and dispersibility in the precursor liquid phase, enabling uniform doping of cerium in the titanium dioxide lattice. Furthermore, the nitrate component can be completely decomposed and removed during subsequent calcination, preventing the introduction of residual impurities that could interfere with the crystal structure and surface properties of the support. Controlling the molar ratio of cerium to titanium within the range of 3% to 8% ensures sufficient cerium ions to induce lattice distortion in TiO2 through lattice doping and grain boundary segregation, effectively reducing the oxygen vacancy formation energy and increasing the defect concentration of the support. Simultaneously, it leverages the properties of cerium... 3+ / Ce 4+ The reversible valence state cycle anchors the oxygen vacancy structure, inhibits vacancy migration and annihilation during the reaction, and enhances the electronic interaction between the support and the platinum active component.
[0035] In this invention, the calcination temperature of the high-temperature calcination treatment is 350~450℃ and the calcination time is 1~3h; the calcination temperature of the high-temperature calcination treatment is 400℃ and the calcination time is 2h.
[0036] Specifically, the washed and dried reaction product is placed in a muffle furnace and calcined at a constant temperature of 350~450℃ for 1~3 hours to remove residual organic matter and fluoride ions.
[0037] It is understood that the high-temperature calcination treatment can, on the one hand, decompose and remove the residual organic components and adsorbed fluorine ion impurities in the cerium-doped TiO2 precursor prepared by hydrothermal treatment, avoiding the interference of impurity residues on the subsequent construction efficiency of oxygen vacancies and the interfacial bonding effect between platinum active components and the support; on the other hand, it can promote the precursor to crystallize from an amorphous form into an anatase phase structure with suitable crystallinity, so that cerium ions can be more stably embedded in the TiO2 lattice and form a uniform doping distribution.
[0038] In this invention, the atmosphere for the low-temperature hydrogen plasma treatment is high-purity hydrogen, the chamber pressure is 20~60Pa, the radio frequency plasma power is 100~200W, and the treatment time is 10~30min; the radio frequency plasma power is 150W, and the treatment time is 20min.
[0039] Specifically, the cerium-doped TiO2 nanosheets are laid flat in the plasma reaction chamber, evacuated to below 10 Pa, and then high-purity hydrogen is introduced. The chamber pressure is controlled to be maintained between 20 and 60 Pa, the radio frequency plasma power is adjusted to 100 to 200 W, and the process is carried out at room temperature for 10 to 30 minutes. After the process is completed, the plasma power supply is turned off, and the nanosheets are removed after the temperature drops to room temperature under argon protection.
[0040] Understandably, low-temperature hydrogen plasma treatment can use high-energy active hydrogen species to etch and reduce the surface of cerium-doped TiO2 nanosheets at room temperature. Without inducing grain sintering and maintaining the sheet-like morphology and high specific surface area, it introduces high-density unsaturated coordination sites and shallow oxygen vacancies into the surface layer of the support, breaking through the bottleneck of traditional one-step high-temperature hydrogen reduction, which is prone to grain growth and limited surface defect concentration. At the same time, the pre-constructed surface defects can serve as a fast channel for hydrogen atoms to diffuse into the bulk phase during the subsequent high-temperature hydrogen-argon reduction process, promoting the uniform generation of bulk oxygen vacancies.
[0041] In this invention, the atmosphere for the high-temperature hydrogen-argon gas reduction treatment is a hydrogen-argon mixed gas, the treatment temperature is 700~950℃, the heating rate is 3~8℃ / min, and the holding time is 3~5h; the preferred treatment temperature is 850℃, the heating rate is 5℃ / min, and the holding time is 4h.
[0042] Specifically, the sample treated with low-temperature hydrogen plasma is transferred into a tube furnace, and a hydrogen-argon mixture with a volume fraction of 5% is introduced at a flow rate of 100 mL / min. The temperature is raised to 700-950°C at a rate of 3-8°C / min, and then held at that temperature for 3-5 hours. The sample is then removed after the tube furnace has cooled to room temperature naturally.
[0043] Understandably, the high-temperature hydrogen-argon gas reduction treatment utilizes the high-temperature environment to drive hydrogen atoms to diffuse into the support along pre-constructed surface defect channels. Through hydrogen reduction, some oxygen atoms in the TiO2 lattice are removed, forming a large number of oxygen vacancies within the support bulk phase. These vacancies, together with the high-density surface defects, constitute a surface-bulk phase gradient defect structure. Simultaneously, the high-temperature environment promotes valence state transformation and grain boundary segregation of doped cerium ions, leveraging Ce... 3+ / Ce 4+ The reversible valence cycle and lattice distortion effect anchor the oxygen vacancy structure, effectively suppressing the migration and annihilation of oxygen vacancies during high temperature and subsequent reactions, and improving the long-term stability of the defect structure.
[0044] In this invention, the platinum loading of the rare earth-doped modified black titanium dioxide supported Pt catalyst is 1% to 3% of the total catalyst mass; preferably, the platinum loading of the rare earth-doped modified black titanium dioxide supported Pt catalyst is 2% of the total catalyst mass.
[0045] In this invention, the visible light-induced reduction specifically refers to: The first mixture was irradiated with visible light with a wavelength ≥420nm, and the incident light intensity was controlled to be 100~200mW / cm². 2A sodium borohydride aqueous solution is added dropwise during irradiation, wherein the molar ratio of sodium borohydride to platinum in the first mixture is (5~20):1, and the addition time is 8~20 min; after the addition is completed, the light is maintained and the reaction is stirred for 1.5~2.5 h; the incident light intensity is preferably 150 mW / cm². 2 The preferred molar ratio of sodium borohydride to platinum in the first mixture is 10:1, the preferred dropping time is 15 min, and the preferred stirring reaction time is 2 h.
[0046] Specifically, the first mixture is placed in a visible light reaction device and irradiated with visible light with a wavelength ≥420nm, with the incident light intensity controlled at 100~200mW / cm². 2 While irradiating with light and stirring, slowly add an aqueous solution of sodium borohydride. The molar ratio of sodium borohydride to platinum in the platinum precursor is (5~20):1. The addition time is controlled at 8~20 min. After the addition is completed, continue to irradiate with light and stir for 1.5~2.5 h.
[0047] It is understood that the visible light-induced reduction method used in this invention utilizes the visible light response characteristics of cerium-doped black titanium dioxide. Under visible light irradiation, photogenerated electrons are excited and directionally enriched on oxygen vacancies and cerium active sites on the support surface. This drives the platinum precursor to preferentially nucleate and grow in situ at the defect interface. Combined with the slow chemical reduction effect of sodium borohydride, the average particle size of platinum nanoparticles is significantly reduced and their size distribution is narrowed, greatly improving the dispersion of active components and the exposure of active sites. At the same time, this process can strengthen the metal-support interaction between platinum and the support, promote interfacial electron transfer, increase the proportion of zero-valent platinum on the catalyst surface, and enhance the oxidative activation ability of primary hydroxyl groups of glycerol molecules.
[0048] The present invention also provides a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0049] The present invention also provides an application of rare earth-doped modified black titanium dioxide supported Pt catalyst in the catalytic oxidation of glycerol.
[0050] Specifically, the rare earth-doped modified black titanium dioxide supported Pt catalyst is used in the selective oxidation of glycerol to prepare glyceric acid under alkali-free neutral conditions. In specific applications, the catalyst and 0.4~0.6 mol / L glycerol aqueous solution are added to the reaction vessel at a solid-liquid ratio of 1g:(100~200)mL. Oxygen is continuously introduced at a flow rate of 100~200mL / min under normal pressure at 50~70℃ and the reaction is stirred for 4~8h. After the reaction is completed, the catalyst can be separated and recovered by simple filtration. The filtrate is then purified to obtain the glyceric acid product. Example 1 S1. Tetrabutyl titanate and 40% hydrofluoric acid were mixed at a volume ratio of 20:2. Cerium nitrate hexahydrate was added at the same time, and the molar ratio of cerium to titanium was controlled at 3%. The mixture was stirred vigorously for 5 minutes to obtain the precursor solution. S2. The precursor solution was transferred to a high-pressure reactor, sealed, and hydrothermally reacted at 160°C for 18 hours. After the reaction was completed, the product was naturally cooled to room temperature. The product was washed twice by alternating centrifugation with anhydrous ethanol and deionized water, and dried at 60°C for 8 hours. The dried product was placed in a muffle furnace and calcined at 350°C for 1 hour to obtain cerium-doped TiO2 nanosheets. S3. The cerium-doped TiO2 nanosheets are spread flat in the plasma reaction chamber, evacuated to below 10 Pa, and then high-purity hydrogen is introduced. The chamber pressure is controlled between 20 and 60 Pa, the radio frequency plasma power is 100 W, and the treatment is carried out at room temperature for 10 min. After the treatment is completed, the plasma power supply is turned off, and the nanosheets are removed after cooling to room temperature under argon protection. They are then transferred to a tube furnace, and a hydrogen-argon mixed gas with a volume fraction of 3% is introduced. The temperature is raised to 700°C at a heating rate of 3°C / min, and calcined at this temperature for 3 h. After the tube furnace cools naturally to room temperature, the nanosheets are removed to obtain the cerium-doped TiO2 support. S4. The cerium-doped TiO2 support and anhydrous ethanol are mixed at a solid-liquid ratio of 1g:100mL, and magnetically stirred for 20min. Then, chloroplatinate aqueous solution is added, with the amount added being 1% of the total mass of the catalyst based on the platinum loading. Stirring is continued for 20min under light-protected conditions to obtain the first mixture. S5. Place the first mixture in a visible light reaction device and irradiate it with visible light with a wavelength ≥420nm, controlling the incident light intensity to be 100mW / cm². 2 A sodium borohydride aqueous solution was slowly added dropwise while the mixture was irradiated and stirred. The molar ratio of sodium borohydride to platinum in the platinum precursor was 5:1, and the addition time was controlled at 8 min. After the addition was completed, the mixture was irradiated and stirred for another 1.5 h. After the reaction was completed, the product was separated by centrifugation, washed twice alternately with distilled water and anhydrous ethanol, and dried at 50 °C for 10 h to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0051] Example 2 S1. Tetrabutyl titanate and 40% hydrofluoric acid by mass fraction are mixed at a volume ratio of 25:3. Cerium nitrate hexahydrate is added at the same time, and the molar ratio of cerium to titanium is controlled at 5%. The mixture is stirred vigorously for 10 minutes to obtain the precursor solution. S2. The precursor solution was transferred to a high-pressure reactor, sealed, and hydrothermally reacted at 180°C for 24 hours. After the reaction was completed, the product was naturally cooled to room temperature. The reaction product was washed three times by alternating centrifugation with anhydrous ethanol and deionized water, and dried at 70°C for 12 hours. The dried reaction product was placed in a muffle furnace and calcined at 400°C for 2 hours to obtain cerium-doped TiO2 nanosheets. S3. The cerium-doped TiO2 nanosheets are spread in a plasma reaction chamber, evacuated to below 10 Pa, and then high-purity hydrogen is introduced. The chamber pressure is controlled between 20 and 60 Pa, the radio frequency plasma power is 150 W, and the treatment is carried out at room temperature for 20 min. After the treatment is completed, the plasma power supply is turned off, and the nanosheets are removed after cooling to room temperature under argon protection. They are then transferred to a tube furnace, and a hydrogen-argon mixed gas with a volume fraction of 8% is introduced. The gas flow rate is controlled at 100 mL / min, and the temperature is raised to 850°C at a heating rate of 5°C / min. The temperature is held for calcination for 4 h, and the nanosheets are removed after the tube furnace has cooled to room temperature naturally to obtain the cerium-doped TiO2 support. S4. The cerium-doped TiO2 support and anhydrous ethanol are mixed at a solid-liquid ratio of 1g:150mL, and magnetically stirred for 30min. Chloroplatinate aqueous solution is added, and the amount added is measured as 2% of the total mass of the catalyst with platinum loading. Stirring is continued for 30min under light-protected conditions to obtain the first mixture. S5. Place the first mixture in a visible light reaction device and irradiate it with visible light with a wavelength ≥420nm, controlling the incident light intensity to be 150mW / cm². 2 A sodium borohydride aqueous solution was slowly added dropwise while the mixture was irradiated and stirred. The molar ratio of sodium borohydride to platinum in the platinum precursor was 10:1, and the addition time was controlled at 15 min. After the addition was completed, the mixture was irradiated and stirred for another 2 h. After the reaction was completed, the product was separated by centrifugation, washed three times alternately with distilled water and anhydrous ethanol, and dried at 60℃ for 12 h to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0052] Example 3 S1. Tetrabutyl titanate and 40% hydrofluoric acid were mixed at a volume ratio of 30:4. Cerium nitrate hexahydrate was added at the same time, and the molar ratio of cerium to titanium was controlled at 8%. The mixture was stirred vigorously for 15 minutes to obtain the precursor solution. S2. The precursor solution was transferred to a high-pressure reactor, sealed, and hydrothermally reacted at 200℃ for 30h. After the reaction was completed, it was naturally cooled to room temperature. The reaction product was washed 4 times by alternating centrifugation with anhydrous ethanol and deionized water, and dried at 80℃ for 16h. The dried reaction product was placed in a muffle furnace and calcined at 450℃ for 3h to obtain cerium-doped TiO2 nanosheets. S3. The cerium-doped TiO2 nanosheets are spread in a plasma reaction chamber, evacuated to below 10 Pa, and then high-purity hydrogen is introduced. The chamber pressure is controlled between 20 and 60 Pa, the radio frequency plasma power is 200 W, and the treatment is carried out at room temperature for 30 min. After the treatment is completed, the plasma power supply is turned off, and the nanosheets are removed after cooling to room temperature under argon protection. They are then transferred to a tube furnace, and a hydrogen-argon mixed gas with a volume fraction of 10% is introduced. The temperature is raised to 950°C at a heating rate of 8°C / min and held for calcination for 5 h. After the tube furnace cools naturally to room temperature, the nanosheets are removed to obtain the cerium-doped TiO2 support. S4. The cerium-doped TiO2 support is mixed with anhydrous ethanol at a solid-liquid ratio of 1g:200mL, and magnetically stirred for 40min. Then, chloroplatinate aqueous solution is added, with the amount added being 3% of the total mass of the catalyst based on the platinum loading. Stirring is continued for 40min under light-protected conditions to obtain the first mixture. S5. Place the first mixture in a visible light reaction device and irradiate it with visible light with a wavelength ≥420nm, controlling the incident light intensity to be 200mW / cm². 2 A sodium borohydride aqueous solution was slowly added dropwise while irradiating and stirring. The molar ratio of sodium borohydride to platinum in the platinum precursor was 20:1, and the addition time was controlled at 20 min. After the addition was completed, the reaction was continued with irradiation and stirring for 2.5 h. After the reaction was completed, the product was separated by centrifugation, washed four times alternately with distilled water and anhydrous ethanol, and dried at 70 ℃ for 14 h to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
[0053] Comparative Example 1 (Sheet-like Pt / B-TiO2 catalyst prepared by patent CN117504843A) S1. Tetrabutyl titanate and 40wt% hydrofluoric acid were mixed at a volume ratio of 25:3. After stirring vigorously for 10 min, the mixture was transferred to a high-pressure reactor and hydrothermally reacted at 180℃ for 24 h. The product was washed three times by alternating centrifugation with anhydrous ethanol and deionized water, dried at 60℃ for 12 h, and calcined in air at 400℃ for 2 h to obtain the precursor. S2. The precursor was placed directly in a tube furnace and a hydrogen-argon mixture with a volume fraction of 5% was introduced. The mixture was reduced at 900℃ for 4 hours to obtain the carrier. S3. Take 0.4275g of support and disperse it in 60mL of anhydrous ethanol. After stirring and dispersing for 30min, add 6mL of 0.01g / mL potassium chloroplatinate aqueous solution and continue stirring and adsorption for 30min. Protect the light throughout the process. Add 2.5mL of deionized water containing 0.01g NaBH4 at one time. Stir and react for 3h, then wash and dry at 60℃ to obtain the catalyst.
[0054] Comparative Example 2 (compared to Comparative Example 1, a cerium doping modification step was added). S1. Tetrabutyl titanate and 40wt% hydrofluoric acid were mixed at a volume ratio of 25:3. Cerium nitrate hexahydrate was added simultaneously. The molar ratio of Ce to Ti was controlled at 5%. After vigorous stirring for 10 min, the mixture was transferred to a high-pressure reactor and hydrothermally reacted at 180℃ for 24 h. The product was washed three times by alternating centrifugation with anhydrous ethanol and deionized water, dried at 60℃ for 12 h, and calcined in air at 400℃ for 2 h to obtain the precursor. S2. The precursor was placed directly in a tube furnace and a hydrogen-argon mixture with a volume fraction of 5% was introduced. The mixture was reduced at 900℃ for 4 hours to obtain the carrier. S3. Take 0.4275g of support and disperse it in 60mL of anhydrous ethanol. After stirring and dispersing for 30min, add 6mL of 0.01g / mL potassium chloroplatinate aqueous solution and continue stirring and adsorption for 30min. Protect the light throughout the process. Add 2.5mL of deionized water containing 0.01g NaBH4 at one time. Stir and react for 3h, then wash and dry at 60℃ to obtain the catalyst.
[0055] Comparative Example 3 (without the light-induction step compared to Example 2) S1. Tetrabutyl titanate and 40wt% hydrofluoric acid were mixed at a volume ratio of 25:3. Cerium nitrate hexahydrate was added simultaneously. The molar ratio of Ce to Ti was controlled at 5%. After vigorous stirring for 10 min, the mixture was transferred to a high-pressure reactor and hydrothermally reacted at 180℃ for 24 h. The product was washed three times by alternating centrifugation with anhydrous ethanol and deionized water, dried at 60℃ for 12 h, and calcined in air at 400℃ for 2 h to obtain the precursor. S2. The precursor is first subjected to low-temperature hydrogen plasma treatment (cavity pressure 40Pa, radio frequency power 150W, room temperature treatment for 20min), and then placed in a tube furnace and reduced for 4h under the same hydrogen and argon atmosphere at 850℃ to obtain the corresponding carrier.
[0056] S3. Take 0.4275g of support and disperse it in 60mL of anhydrous ethanol. After stirring and dispersing for 30min, add 6mL of 0.01g / mL potassium chloroplatinate aqueous solution and continue stirring and adsorption for 30min. Protect the light throughout the process. Add 2.5mL of deionized water containing 0.01g NaBH4 at one time. Stir and react for 3h, then wash and dry at 60℃ to obtain the catalyst.
[0057] Effect test Characterization of the carrier: The average grain size of the (101) crystal plane of TiO2 anatase phase was calculated by X-ray diffraction combined with Scherrer's formula; the intensity of the oxygen vacancy characteristic peak at g=2.003 was measured by electron paramagnetic resonance spectroscopy (EPR) and converted into the molar concentration of oxygen vacancy.
[0058] Catalyst characterization: The average particle size of more than 200 Pt particles was statistically analyzed using transmission electron microscopy; the dispersion of the Pt active component was tested using CO pulse adsorption method.
[0059] Catalytic performance test: 30 mL of 540 mmol / L glycerol aqueous solution was added to a 100 mL three-necked flask, followed by 0.2 g of catalyst. The mixture was stirred in an oil bath at 60 °C and oxygen was introduced at a flow rate of 150 mL / min for 6 h. The composition of the product was detected by high performance liquid chromatography, and the glycerol conversion rate and glyceric acid selectivity were calculated. After the catalyst was recycled 5 times, the glycerol conversion rate retention rate was calculated.
[0060] The test results are shown in Table 1: Table 1 Results of Effect Test As can be seen from the comparison of Comparative Example 1 and Comparative Example 2, single cerium doping can reduce the oxygen vacancy formation energy through the lattice distortion effect, thereby increasing the oxygen vacancy concentration of the support by 46.4% and slightly refining the grain size, although the increase is limited. Comparing Comparative Example 2 and Comparative Example 3, at the same high-temperature reduction temperature, the addition of low-temperature hydrogen plasma treatment increased the oxygen vacancy concentration of the support from 18.3 μmol / g to 28.7 μmol / g, an increase of 56.8%, while the TiO2 grain size did not increase, but remained at a relatively low level of 14.7 nm. This proves that low-temperature plasma can construct surface defect channels at room temperature, promoting the diffusion of hydrogen atoms into the bulk phase, significantly increasing the oxygen vacancy concentration without increasing the reduction temperature, fundamentally avoiding grain sintering caused by high-temperature treatment. Combined with the cycling performance data, the conversion rate retention rate of Comparative Example 3 is 10.6 percentage points higher than that of Comparative Example 2, further demonstrating that the lattice segregation of cerium ions and the gradient oxygen vacancy structure synergistically anchor the defect sites, effectively suppressing oxygen vacancy annihilation during the reaction process and improving the long-term stability of the support structure.
[0061] Comparing Comparative Example 3 and Example 2, it can be seen that the support structures of the two are completely identical, with only the Pt loading process differing. After visible light-induced reduction, the average Pt particle size decreased from 2.4 nm to 1.6 nm, and the Pt dispersion increased from 51% to 72%, demonstrating that photogenerated electrons are directionally enriched at the defect sites of the support, driving the Pt precursor to preferentially nucleate and grow in situ at the interface, effectively avoiding particle agglomeration caused by homogeneous liquid-phase reduction, and significantly increasing the exposure of active sites. In terms of corresponding catalytic performance, the glycerol conversion rate increased from 67.2% to 76.4%, and the glyceric acid selectivity increased from 75.3% to 78.2%, indicating that the in-situ grown Pt particles formed a stronger metal-support interaction with the support, enhancing the interfacial electron transfer effect and significantly improving the oxidation activation ability of the primary hydroxyl group of glycerol and the product directional selectivity. Simultaneously, the conversion retention rate after 5 cycles increased from 79.1% to 90.8%, demonstrating that the strong interaction effectively inhibited the shedding and agglomeration of Pt particles during the reaction, and the catalyst cycle stability was significantly improved.
[0062] Compared with Comparative Example 1, the carrier prepared in Example 2 of this invention has an increased oxygen vacancy concentration of 129.6%, an increased Pt dispersion of 89.5%, an increased glycerol conversion rate of 48.9%, an increased glyceric acid selectivity of 8.2 percentage points, and an increased performance retention rate after 5 cycles of 30.6 percentage points.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a rare earth-doped modified black titanium dioxide-supported Pt catalyst, characterized in that, The preparation steps include the following: Tetrabutyl titanate was mixed with hydrofluoric acid, and a cerium source was added and stirred to obtain a precursor solution. The precursor solution was subjected to a hydrothermal reaction, and the reaction product was washed, dried, and then calcined at high temperature to obtain cerium-doped TiO2 nanosheets. The cerium-doped TiO2 nanosheets were subjected to low-temperature hydrogen plasma treatment followed by high-temperature hydrogen-argon gas reduction treatment to obtain a cerium-doped TiO2 support. The cerium-doped TiO2 support was mixed with ethanol and then added to an aqueous chloroplatinate solution and stirred in the dark to obtain a first mixture. The first mixture was subjected to visible light-induced reduction and post-processing to obtain a rare earth-doped modified black titanium dioxide supported Pt catalyst.
2. The method for preparing rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The volume ratio of tetrabutyl titanate to hydrofluoric acid is (20~30):(2~4), and the mass fraction of hydrofluoric acid is 40%.
3. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The cerium source is cerium nitrate hexahydrate, and the molar ratio of cerium to titanium in the rare earth-doped modified black titanium dioxide supported Pt catalyst is 3%~8%.
4. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The calcination temperature for the high-temperature calcination treatment is 350~450℃, and the calcination time is 1~3h.
5. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The atmosphere for the low-temperature hydrogen plasma treatment is hydrogen, the chamber pressure is 20~60Pa, the radio frequency plasma power is 100~200W, and the treatment time is 10~30min.
6. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The atmosphere for the high-temperature hydrogen-argon gas reduction treatment is a hydrogen-argon mixed gas, the treatment temperature is 700~950℃, the heating rate is 3~8℃ / min, and the holding time is 3~5h.
7. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The platinum loading of the rare earth-doped modified black titanium dioxide supported Pt catalyst is 1% to 3% of the total catalyst mass.
8. The method for preparing the rare earth-doped modified black titanium dioxide supported Pt catalyst according to claim 1, characterized in that, The visible light-induced reduction specifically refers to: The first mixture was irradiated with visible light with a wavelength ≥420nm, and the incident light intensity was controlled to be 100~200mW / cm². 2 Sodium borohydride aqueous solution is added dropwise during irradiation, wherein the molar ratio of sodium borohydride to platinum in the first mixture is (5~20):1, and the addition time is 8~20 min; after the addition is completed, the light is maintained and the reaction is stirred for 1.5~2.5 h.
9. A rare earth-doped modified black titanium dioxide supported Pt catalyst, characterized in that, It is prepared by the method for preparing rare earth-doped modified black titanium dioxide supported Pt catalyst according to any one of claims 1-8.
10. The application of the rare earth-doped modified black titanium dioxide supported Pt catalyst as described in claim 9 in the catalytic oxidation of glycerol.
Citation Information
Patent Citations
Glycerin selective oxidation supported catalyst, preparation method and application
CN117504843A
